Assessment of some heavy metals in various aquatic plants of Al-Hawizeh Marsh, southern of Iraq - Dunya A. Al-Abbawy; BASIM M. HUBAIN AL-THAHAIBAWI; ITHAR K.A. AL-MAYALY; KADHIM H. YOUNIS (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Al-Abbawy DAH, Al-Thahaibawi BMH, Al-Mayaly IKA, Younis KH. 2021. Assessment of some heavy metals in various aquatic plants of Al-Hawizeh Marsh, southern of Iraq. Biodiversitas 22: 338-345. In order to describe the degree of contamination of aquatic environments in Iraq, heavy metals analysis (Fe, Ni, Cr, Cd, Pb, and Zn) was conducted for six aquatic macrophytes from different locations of Al-Hawizeh Marsh in southern Iraq. The six species were Azolla filiculoides (floating plant), Ceratophyllum demersum, Potamogeton pectinatus, Najas marina (submerged plants), Phragmites australis, and Typha domingensis (emergent plants). The results indicate that cadmium, chromium, and iron concentrations in aquatic plants were above the World Health Organization (WHO). In contrast, zinc, copper, and lead were within the allowable limits. C. demersum and N. marina showed higher concentrations of heavy metal accumulation than the other aquatic plants. The concentration of heavy metals in plant tissues during the summer months was higher than in the different seasons. C. demersum and N. marina showed higher concentrations of heavy metal accumulation than the other aquatic plants. Heavy metal bioconcentration (BCF) was calculated to assess heavy metals bioaccumulation in the aquatic plants.